Malign Differentiation of a Large Buschke Loewenstein Tumor in Penis - Akdag, Osman; Yildiran, Gokce (The Surgery Journal, 2018)
Buschke–Loewenstein tumor (BLT) is a giant condyloma acuminatum which is very rare and commonly affects the anogenital region. The malignant transformation and localization in penis is very rare. This article aims to present a case with BLT with malignant transformation in penis.A 59-year-old male patient was referred, who has have been suffering from a cauliflower-like lesion in the penis for 8 years. Biopsies revealed a BLT with malignant transformation. The lesion was excised largely and reconstructed with local flaps and skin grafts.Defined by Buschke and Loewenstein in 1925, giant condyloma acuminatum is a rare and important disorder because of the sexually transmitting capability.
Keywords: Buschke–Loewenstein tumor; condyloma acuminate; malignant transformation; penis